MERUBAH PERUNTUKAN WAKAF DALAM PERSPEKTIF EMPAT MADZHAB - Hakim, Lukman (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2015)
Waqf is commanded in Islam for the moslem's prosperity in tackling poverty. It is intended for families who need help. In various literatures, it can be found that in the early Islamic period, Waqf has been known in two forms. The first, Waqf that is dedicated to the particular person. The second,Waqf that is used for the public purpose. Waqf issues are typically associated with the unclear status of donated property .It is happened before the formal certificate or formal registration certificate of Waqf is made for obtaining Waqf certificate from the authority. Even, the certified property is usually still claimed by the heir. Based on Imam Mujtahid, there are some different opinions in changing the designation of Waqf objects. Imam Hambali allowed the sale and replacement of waqf but Imam Syafi'i banned the sale and replacement implicitly. Imam Maliki found that Waqf objects can be sold in three circumstances. The first, if the benefactor requires sale when he was donating. The second , if Waqf is not used anymore. The third, if the replacement will bring the greater benefits and results.